A theory on the liquid structures of molecular dimers based on the BBGKY hierarchy: the direct correlation function. (3rd June 2022) - Lee, Lloyd L.
ABSTRACT: We propose a molecular theory for fluids of structured molecules based on the Born-Bogoliubov-Green-Kirkwood-Yvon (BBGKY) hierarchy for classical fluids. We treat the polyatomic molecules as an N-body mixture of its constituent moieties. The reassembly of these chemical units into the original molecules is achieved via the site-site interaction potentials. To find the usual total correlations and direct correlations, we incorporate the Lebowitz-Percus functional derivatives, i.e. the 'fluctuation-compressibility' derivatives into the first member of the BBGKY. This enables us to construct a generalised Ornstein-Zernike equation for the system of dimeric molecules. We are able to separate out from the resulting equation a part that is identified as the direct correlation functions. This equation involves higher order correlations, namely the triplet correlation functions. We contrast this direct correlation with those from the earlier reference interaction site model (RISM) and exhibit the differences between the two approaches. A new theoretical framework is established, as an alternative to other current theories for polyatomic molecular fluids. GRAPHICAL ABSTRACT: UF0001